A New Statistical Parameter for Identifying the Main Transition Velocities in Bubble Columns*. Issue 11 (15th October 2015) - Nedeltchev, Stoyan; Rabha, Swapna; Hampel, Uwe; Schubert, Markus
Abstract: The identification of the main flow regime boundaries in bubble columns is essential since the degrees of mixing and mass and heat transfer vary with the flow regime. In this work, a new statistical parameter was extracted from the time series of the cross‐sectional averaged gas holdup. The measurements were performed in bubble columns by means of conductivity wire‐mesh sensors at very high sampling frequency. The columns were operated with an air/deionized water system under ambient conditions. As a flow regime indicator, a new dimensionless statistical parameter called "relative maximum number of visits in a region" was introduced. This new parameter is a function of the difference between the maximum numbers of visits in a region, calculated from two different division schemes of the signal range. Abstract : A new dimensionless statistical parameter that is independent of any other parameter was developed to characterize the main flow regime boundaries in bubble columns. Based on the two distinct local minima in the profile of the new index, the two main transition velocities in both a small and a large bubble column were identified.